Modified chelating resin as well as preparation method and application thereof

By pretreating the chelating resin and modifying it with copper ion loading, the ammonia nitrogen adsorption efficiency was improved, solving the problems of low ammonia nitrogen adsorption efficiency and interference from coexisting ions in the existing technology, and achieving efficient and low-cost wastewater treatment.

CN120865565APending Publication Date: 2025-10-31SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511039441.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing chelating resins have low ammonia nitrogen adsorption efficiency and are easily affected by coexisting ions, especially the competitive adsorption of Ca2+ and Mg2+. Furthermore, traditional modification methods are complex, have poor regeneration performance, and are costly.

Method used

By pretreating the chelating resin, loading it with copper ions, and treating it with low-concentration alkali, a synergistic mechanism between the copper ion coordination activation layer and the alkaline surface modification is constructed to improve the surface properties of the resin and form a modified chelating resin.

Benefits of technology

It significantly improved the ammonia nitrogen adsorption capacity to over 3.6 mg/g, reduced interference from coexisting ions, maintained high efficiency and stability, and reduced treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater treatment and recycling, and discloses modified chelate resin as well as a preparation method and application thereof. The method comprises the following steps: (1) sequentially carrying out first soaking, second soaking and third soaking on chelate resin in a first NaOH solution, an HCl solution and a second NaOH solution respectively, and carrying out suction filtration and drying to obtain pretreated resin; (2) mixing the pretreated resin with a CuSO4 solution to perform first contact reaction for 2-4 hours, and then sequentially performing washing, suction filtration and drying to obtain copper-loaded chelate resin; and (3) mixing the copper-loaded chelate resin with a third NaOH solution, carrying out second contact reaction for 5-30 minutes, and then sequentially washing, carrying out suction filtration and drying to obtain the modified chelate resin. The modified chelate resin obtained through the method has excellent regeneration performance and stability, the selective adsorption capacity of the chelate resin to target ions is improved, and meanwhile interference of coexisting ions is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment and resource utilization technology, specifically to a modified chelating resin, its preparation method, and its application. Background Technology

[0002] In the field of wastewater treatment, chelating resins have become key materials for resource recovery and pollution control due to the high selective adsorption capacity of their functional groups for specific metal ions. For example, aminophosphonic acid-based chelating resins exhibit excellent performance in the adsorption of transition metal ions such as copper and nickel due to their stable coordination structure, but their selective adsorption capacity for ammonia nitrogen still has significant limitations.

[0003] Current research largely focuses on the selective adsorption of heavy metal ions (such as the resin modification scheme disclosed in CN117531549A), while optimization for ammonia nitrogen adsorption is significantly insufficient. In actual wastewater systems, multivalent cations (such as Ca) are more prevalent. 2+ Mg 2+ ) and ammonia nitrogen (NH4) + The competitive adsorption effect formed by the resin leads to the non-selective occupation of the resin active sites, which severely restricts the adsorption efficiency of ammonia nitrogen.

[0004] Liu et al. (Adsorption of ammonia nitrogen and phenol onto the lignite surface, 2021, Journal of Hazardous Materials) studied the effect of hardness ions on the adsorption of ammonia nitrogen and phenol on lignite. Experiments showed that Ca... 2+ and Mg 2+ The presence of these ions significantly interferes with ammonia nitrogen adsorption, and this interference increases with the increase of hardness ion concentration.

[0005] Oliver et al. (Nutrient removal from secondary wastewater effluent by adsorption, 2024, Water Sci Technol) provided research data on the interference of hardness ions on ammonia nitrogen adsorption, pointing out that Ca... 2+ Ions significantly interfere with the adsorption of ammonia nitrogen, causing the adsorption capacity to decrease from 28 mg to 16 mg. This problem of interference from coexisting ions has not been systematically solved in the existing technology, which greatly limits the practical application of chelating resins.

[0006] Furthermore, existing modification technologies have inherent drawbacks: while chemical grafting or physical loading of metal oxides can enhance adsorption sites, they generally suffer from complex preparation processes, poor regeneration performance, and high costs (e.g., acyl chloride modification requires multiple organic reactions). Traditional modified resins are easily affected by coexisting ions during dynamic adsorption, resulting in insufficient adsorption capacity and stability, especially in low-concentration multi-component wastewater (ammonia nitrogen <20 mg / L).

[0007] Therefore, it is necessary to develop a method that can simultaneously enhance the target ion (NH4+). + The development of chelating resin modification methods that achieve selective adsorption capacity, significantly suppress interference from coexisting ions, and possess high efficiency, stability, and low-cost regeneration has become a key technical challenge that urgently needs to be overcome in this field. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems in the prior art, such as poor regeneration performance, high cost, and easy influence of competitive adsorption by ammonia nitrogen and calcium and magnesium ions on the adsorption effect of chelating resins with chemical grafting or physical loading of metal oxides.

[0009] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a modified chelating resin, the method comprising the following steps:

[0010] (1) The chelating resin was soaked in the first NaOH solution, the second NaOH solution and the third NaOH solution respectively, and then filtered and dried to obtain the pretreated resin.

[0011] (2) The pretreated resin is mixed with CuSO4 solution and subjected to a first contact reaction for 2-4 hours, and then washed, filtered and dried to obtain copper-loaded chelating resin.

[0012] (3) The copper-loaded chelating resin is mixed with the third NaOH solution for a second contact reaction for 5-30 min, and then washed, filtered and dried in sequence to obtain the modified chelating resin.

[0013] The concentration of the third NaOH solution is 0.001-0.01 mol / L.

[0014] The second aspect of the present invention provides a modified chelating resin prepared by the method described in the first aspect above.

[0015] A third aspect of the present invention provides the application of the modified chelating resin described in the second aspect above in wastewater treatment.

[0016] Compared with the prior art, the present invention has at least the following advantages:

[0017] (1) The preparation method provided by this invention synergistically regulates the surface properties of the resin through pretreatment, copper ion loading, and low-concentration short-time alkali treatment, constructing a synergistic mechanism between the copper ion coordination activation layer and the alkaline surface modification. While maintaining the adsorption performance of heavy metal ions, it increases the adsorption capacity of ammonia nitrogen to more than 3.6 mg / g. Compared with traditional technologies, the adsorption capacity is generally increased by two times, which can significantly improve the input-recovery ratio and further reduce costs. Moreover, after three adsorption-desorption cycle tests, the modified resin can maintain more than 75% of the initial adsorption capacity, significantly improving the technical contradiction of difficulty in achieving both regeneration performance and adsorption capacity in traditional methods.

[0018] (2) The modified chelating resin prepared by this invention significantly improves the selective adsorption capacity of the chelating resin for target ions (such as ammonium) while reducing the interference of coexisting ions (calcium, magnesium). This method is simple and has high regeneration efficiency, providing a more practical solution for complex wastewater treatment. Detailed Implementation

[0019] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0020] As mentioned above, the first aspect of the present invention provides a method for preparing a modified chelating resin, the method comprising the following steps:

[0021] (1) The chelating resin was soaked in the first NaOH solution, the second NaOH solution and the third NaOH solution respectively, and then filtered and dried to obtain the pretreated resin.

[0022] (2) The pretreated resin is mixed with CuSO4 solution and subjected to a first contact reaction for 2-4 hours, and then washed, filtered and dried to obtain copper-loaded chelating resin.

[0023] (3) The copper-loaded chelating resin is mixed with the third NaOH solution for a second contact reaction for 5-30 min, and then washed, filtered and dried in sequence to obtain the modified chelating resin.

[0024] The concentration of the third NaOH solution is 0.001-0.01 mol / L.

[0025] In a preferred embodiment, in step (1), the chelating resin is a macroporous styrene-based chelating resin.

[0026] Preferably, the macroporous styrene-based chelating resin contains aminophosphate groups and has a crosslinking degree of 8%-12%. In this preferred case, it can better chelate with metallic copper ions to form a stable complex.

[0027] More preferably, the macroporous styrene-based chelating resin has an average pore size of 20-50 nm, determined by mercury porosimetry according to national standard GB / T21650.2-2011.

[0028] In a preferred embodiment, in step (1), the concentration ratio of the first NaOH solution to the second NaOH solution is 1:0.5-1.0. This preferred embodiment is more conducive to the adjustment of the resin pore structure by a weak base, allowing it to be gently converted into a sodium-type ion exchange resin.

[0029] In a preferred embodiment, in step (1), the concentration of the first NaOH solution is 0.5-2.0 mol / L.

[0030] According to a preferred embodiment, in step (1), the concentration of the second NaOH solution is 0.5-1.5 mol / L.

[0031] It should be noted that in this invention, in step (1), the first NaOH solution, the second NaOH solution and the third NaOH solution are all aqueous solutions of NaOH.

[0032] Preferably, in step (1), the concentration of the HCl solution is 0.5-2.0 mol / L.

[0033] In a preferred embodiment, in step (1), the first soaking time is 2-6 hours.

[0034] In a preferred embodiment, in step (1), the second soaking time is 2-6 hours.

[0035] In a preferred embodiment, the third soaking time in step (1) is 8-16 hours.

[0036] Preferably, in step (2), the solid-liquid ratio of the pretreated resin to the CuSO4 solution is 1:200.

[0037] In a preferred embodiment, in step (2), the concentration of the CuSO4 solution is 0.005-0.02 mol / L.

[0038] Preferably, in step (2), the first contact reaction is carried out under oscillating conditions, and at least the following conditions are met: temperature is 15-30°C and rotation speed is 160-240 rpm.

[0039] Preferably, in step (3), the second contact reaction is carried out under oscillating conditions, and at least the following conditions are met: temperature is 15-30°C and rotation speed is 150-220 rpm.

[0040] Preferably, in step (3), the solid-liquid ratio of the copper-loaded chelating resin to the third NaOH solution is 1:100.

[0041] According to a preferred embodiment, in steps (1), (2) and (3), the drying conditions are independent and at least satisfy the following: temperature of 30-50°C and time of 1-3 hours.

[0042] Preferably, in steps (2) and (3), the filtration time is 5-15 min each independently.

[0043] Preferably, the method further includes washing the soaked chelating resin with deionized water until it is neutral after the first soaking, the second soaking, and the third soaking before proceeding with subsequent operations.

[0044] As previously stated, the second aspect of the present invention provides a modified chelating resin prepared by the method described in the first aspect.

[0045] As previously stated, the third aspect of the present invention provides the application of the modified chelating resin described in the second aspect in wastewater treatment.

[0046] Preferably, the wastewater is at least one of domestic sewage, overflow sewage, and initial rainwater.

[0047] Preferably, the wastewater contains Ca 2+ and Mg 2+ The concentrations were 10-80 mg / L and 0-30 mg / L, respectively.

[0048] More preferably, the wastewater contains Ca 2+ and Mg 2+ The concentrations were 15-45 mg / L and 1-20 mg / L, respectively.

[0049] According to a preferred embodiment, the application of the present invention further includes: adjusting the pH of the adsorbed saturated modified chelating resin to 11 with a 1-3 mol / L NaOH solution, and desorbing and regenerating it with a 10-30 g / L NaCl solution, wherein the desorption and regeneration is carried out under oscillation conditions and at least meets the following requirements: time of 2-4 h, temperature of 15-30 °C, and rotation speed of 100-200 rpm.

[0050] The present invention will be described in detail below through examples. Unless otherwise specified, the raw materials used are all commercially available products.

[0051] Chelating resins:

[0052] Chelating resin I: is D418 resin, containing aminophosphonic acid groups, with a crosslinking degree of 8% and an average pore size of 30nm, purchased from Tianjin Xinyue Huamei Co., Ltd.

[0053] Chelating resin II: is D751 resin, containing iminodiacetic acid groups, with a crosslinking degree of 8% and an average pore size of 35nm, purchased from Tianjin Xinyue Huamei Co., Ltd.

[0054] CuSO4 solution: A CuSO4 aqueous solution with a concentration of 0.01 mol / L.

[0055] Example 1

[0056] This embodiment illustrates that the method for preparing modified chelating resin provided by the present invention is carried out according to the following steps:

[0057] (1) The chelating resin (chelating resin I) was first soaked in the first NaOH solution (concentration of 1.0 mol / L) for 4 h, and the soaked chelating resin was washed with deionized water until neutral. Then it was soaked in the HCl solution (concentration of 1.0 mol / L) for 4 h, washed with deionized water until neutral, and finally soaked in the second NaOH solution (concentration of 0.75 mol / L) for 12 h. After filtration for 10 min and drying at 45℃ for 2 h, the pretreated resin was obtained.

[0058] (2) Under the condition of oscillation at 25°C and 200 rpm, the pretreated resin and CuSO4 solution were mixed at a solid-liquid ratio of 1:200 for a first contact reaction for 3 hours, and then washed, filtered (10 min) and dried (dried at 45°C for 2 hours) to obtain copper-loaded chelating resin.

[0059] (3) Under the condition of oscillation at 25℃ and 180 rpm, the copper-loaded chelating resin was mixed with the third NaOH solution (concentration of 0.005 mol / L) at a solid-liquid ratio of 1:100 for a second contact reaction for 20 min. Then, the mixture was washed, filtered (10 min) and dried (dried at 45℃ for 2 h) to obtain the modified chelating resin, named P1.

[0060] Example 2

[0061] This embodiment uses a method similar to that of Embodiment 1, except that the chelating resin used is chelating resin II;

[0062] Finally, the modified chelating resin was obtained and named P2.

[0063] Test Example 1

[0064] The modified chelating resins obtained in the above examples were subjected to simulated ammonia nitrogen wastewater adsorption tests, specifically including:

[0065] Prepare 500 mL of simulated ammonia nitrogen wastewater (NH4) + (Concentration 10 mg / L) Two 200 mL white bottles were filled with 200 mL of simulated ammonia nitrogen wastewater. Then, 0.5 g of D418 resin, 0.5 g of D751 resin, and 0.5 g of the modified chelating resin obtained in the example were weighed and added to the white bottles respectively. The bottles were then placed in a constant temperature shaker at 25 °C and 200 rpm for 3 h for adsorption. The supernatant was collected, and the NH4+ content in the raw water and the supernatant was measured. + The remaining content was used to calculate the resin adsorption capacity, and the results are shown in Table 1.

[0066] Table 1

[0067] <![CDATA[NH4 + Adsorption capacity (mg / L) D418 3.838 P1 9.153 D751 2.44 P2 5.23

[0068] Test Example 2

[0069] The modified chelating resins obtained in the above examples were subjected to simulated overflow wastewater adsorption tests, specifically including:

[0070] Prepare 500 mL of simulated overflow wastewater (NH4) + Content 10mg / L, Ca 2+ Content 30mg / L, Mg 2+ (Content 7.2 mg / L) Two 200 mL white bottles were used to add 200 mL of simulated ammonia nitrogen wastewater to each bottle. Then, 0.5 g of D418 resin and 0.5 g of the modified chelating resin obtained in the example were weighed and added to the white bottles respectively. The bottles were then placed in a constant temperature shaker at 25 °C and 200 rpm for 3 h for adsorption. The supernatant was collected, and the NH4+ content in the raw water and the supernatant was measured. + Ca 2+ Mg 2+ The remaining content was used to calculate the resin adsorption capacity and separation coefficient.

[0071] Regeneration experiment: Under shaking conditions at 25℃ (200 rpm), the pH of the adsorption-saturated D418 resin and the modified chelating resin was adjusted to 11 with 1 mol / L NaOH solution, and then regenerated by desorption with 200 mL of 15 g / L NaCl solution (pH 11) for 2 h. After desorption, the NH4+ content in the supernatant was measured. + Ca 2+ Mg 2+ The content was determined to obtain regenerated D418 resin and regenerated modified chelating resin;

[0072] Multiple adsorption tests: The regenerated D418 resin and the regenerated modified chelating resin were added to 200 mL of simulated overflow wastewater for a second round of adsorption tests. The NH4 content in the simulated overflow wastewater and supernatant was measured. + Ca 2+ Mg 2+ Remaining content;

[0073] Repeat the above regeneration test and multiple rounds of adsorption test.

[0074] The results are shown in Tables 2 and 3.

[0075] Table 2

[0076]

[0077] Table 3

[0078]

[0079] As shown in Table 3, the adsorption capacity of the modified chelating resin prepared in this invention in the third round can still reach more than 75% of that in the first round.

[0080] Test Example 3

[0081] The modified chelating resins obtained in the above examples were subjected to actual wastewater adsorption tests, specifically including:

[0082] Take 1L of actual domestic sewage (the supernatant of the actual sewage after flocculation with polyaluminum chloride (PAC), NH4) + Content 30.828 mg / L, Ca 2+ Content 40.086 mg / L, Mg 2+ (Content 17.986 mg / L) After adding 5 mL of 40 g / L PAC and settling for 20 min, the supernatant was discarded to obtain test water. 200 mL of the test water was added to two 200 mL white bottles. Then, 0.5 g of D418 resin and 0.5 g of the modified chelating resin obtained in the example were weighed and added to the white bottles respectively. The bottles were then placed in a constant temperature shaker at 25℃ and 200 rpm for 3 h for adsorption. The supernatant was collected, and the NH4+ content in the original water and the supernatant was measured. + Ca 2+ Mg 2+ The remaining content was used to calculate the resin adsorption capacity and separation coefficient.

[0083] The results are shown in Table 4.

[0084] Table 4

[0085]

[0086] Test Example 4

[0087] The modified chelating resins obtained in the above examples were subjected to actual wastewater adsorption tests after dilution, specifically including:

[0088] Take the diluted supernatant of actual domestic sewage (NH4) + Content 9.358 mg / L, Ca 2+ Content 18.436 mg / L, Mg 2+ (Content 4.375 mg / L) 200 mL of each solution was added to two 200 mL white bottles. Then, 0.5 g of D418 resin and 0.5 g of the modified chelating resin obtained in the example were weighed and added to the white bottles respectively. The bottles were then placed in a constant temperature shaker at 25℃ and 200 rpm for 3 hours for adsorption. The supernatant was collected, and the NH4+ content in the original water and the supernatant was measured. + Ca 2+ Mg 2+ The remaining content was used to calculate the resin adsorption capacity and separation coefficient.

[0089] The results are shown in Table 5.

[0090] Table 5

[0091]

[0092] The results above show that the modified chelating resin obtained by the method provided by this invention exhibits better regeneration performance and stability in multiple adsorption cycles. The adsorption capacity of the modified chelating resin after each cycle remains higher than that of the unmodified chelating resin, and it maintains a high ammonia nitrogen removal efficiency even after multiple uses. Furthermore, the method provided by this invention improves the selective adsorption capacity of the chelating resin for target ions (such as ammonium) while reducing interference from coexisting ions (calcium, magnesium).

[0093] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing modified chelating resin, characterized in that, The method includes the following steps: (1) The chelating resin was soaked in the first NaOH solution, the second NaOH solution and the third NaOH solution respectively, and then filtered and dried to obtain the pretreated resin. (2) The pretreated resin is mixed with CuSO4 solution and subjected to a first contact reaction for 2-4 hours, and then washed, filtered and dried to obtain copper-loaded chelating resin. (3) The copper-loaded chelating resin is mixed with the third NaOH solution for a second contact reaction for 5-30 min, and then washed, filtered and dried in sequence to obtain the modified chelating resin. The concentration of the third NaOH solution is 0.001-0.01 mol / L.

2. The method according to claim 1, characterized in that, In step (1), the chelating resin is a macroporous styrene-based chelating resin.

3. The method according to claim 1 or 2, characterized in that, In step (1), the ratio of the concentration of the first NaOH solution to the concentration of the second NaOH solution is 1:0.5-1.

0.

4. The method according to claim 1 or 2, characterized in that, In step (1), the concentration of the first NaOH solution is 0.5-2.0 mol / L; and / or In step (1), the concentration of the second NaOH solution is 0.5-1.5 mol / L.

5. The method according to claim 1 or 2, characterized in that, In step (1), the first soaking time is 2-6 hours; and / or In step (1), the second soaking time is 2-6 hours; and / or In step (1), the third soaking time is 8-16 hours.

6. The method according to claim 1 or 2, characterized in that, In step (2), the concentration of the CuSO4 solution is 0.005-0.02 mol / L.

7. The method according to claim 1 or 2, characterized in that, In steps (1), (2), and (3), the drying conditions are independent and at least satisfy the following: temperature of 30-50°C and time of 1-3 hours.

8. The modified chelating resin prepared by the method according to any one of claims 1-7.

9. The application of the modified chelating resin according to claim 8 in wastewater treatment.

10. The application according to claim 9, characterized in that, The wastewater contains Ca2 + and Mg2 + The concentrations were 10-80 mg / L and 0-30 mg / L, respectively.

Citation Information

Patent Citations

  • Lithium resource recovery ion exchange resin modification method

    CN117531549A